First report of 16SrII–A phytoplasma associated with witches’ broom in Heliotropium arboreum (Blanco) Mabb. from Xisha Islands, with Halticus minutus as a putative vector - Wang, Bao; Feng, Likai; Qin, Heye; Ji, Xuncong; Duan, Ruijun; Huang, Weikang (Frontiers in Plant Science, 2025)
Heliotropium arboreum (Blanco) Mabb. (syn. Tournefortia argentea), a key pioneer plant in tropical coastal ecosystems, plays a vital role in stabilizing coral islands. In China’s Xisha Islands, H. arboreum exhibited witches’ broom symptoms (leaf deformities, reduced leaf size, floral phyllody). PCR assays were employed—using universal and phytoplasma—specific primers to amplify the 16S rRNA, secY, and secA genes—yielding amplicons of 1,248 bp (PV640668), 779 bp (PV854866), and 440 bp (PV854867), confirming a phytoplasma infection (designated H. arboreum witches’ broom phytoplasma, HaWB). BLASTn analysis showed 100% sequence identity with 16SrII–group phytoplasmas, while phylogenetic and virtual RFLP analyses classified HaWB as a 16SrII–A subgroup strain. Additionally, morphological and molecular analyses of insects collected from symptomatic plants identified Halticus minutus as a putative vector. This is the first report of phytoplasma infecting H. arboreum in China, providing critical insights for disease surveillance in fragile coastal ecosystems.